An Open Trial Examining Dialectical Behavior Therapy Skills and Behavioral Weight Loss for Adults With Emotional Eating and Overweight/Obesity. Issue 4 (July 2022) - Braden, Abby; Redondo, Rachel; Ferrell, Emily; Anderson, LaNaya; Weinandy, Jennifer Grant; Watford, Tanya; Barnhart, Wesley R.
Highlights: Live FREE is a 16-week treatment for self-reported emotional eating and overweight/obesity. Live FREE includes DBT skills and behavioral weight loss techniques. An open trial was conducted as a preliminary investigation of the intervention. Pilot data showed evidence of feasibility and acceptability. BMI, self-reported emotional eating, and emotion regulation improved over the treatment. Abstract: Third-wave cognitive behavioral interventions for weight loss have shown promise. However, sparse data exists on the use of dialectical behavior therapy for weight loss. Adapted dialectical behavior therapy skills programs may be especially well suited for adults who engage in emotional eating and are seeking weight loss. Dialectical behavior therapy is skills-based, shares theoretical links to emotional eating, and is effective in treating binge eating. The current study examined the feasibility, acceptability, and preliminary efficacy of Live FREE: FReedom from Emotional Eating, a 16-session group-based intervention. A total of 87 individuals expressed interest in the program, and 39 adults with overweight/obesity (BMI ≥25) and elevated self-reported emotional eating were enrolled. Live FREE targeted emotional eating in the initial sessions 1–9, and sessions 10–16 focused primarily on behavioral weight loss skills while continuing to reinforce emotion regulation training. Assessments were administered at baseline, posttreatment, and 6-month follow up. Enrolled participants were primarily female (97.4%) and Caucasian (91.7%). Treatment retention was strong with participants attending an average of 14.3 sessions and 89.7% of participants completing the intervention. On average, participants lost 3.00 kg at posttreatment, which was maintained at follow-up. Intent-to-treat analyses showed improvements in key outcome variables (self-reported emotional eating, BMI, emotion regulation) over the course of the intervention. Combining dialectical behavior therapy skills with conventional behavioral weight loss techniques may be an effective intervention for adults with overweight/obesity who report elevated emotional eating.